2019
DOI: 10.1109/access.2019.2953779
|View full text |Cite
|
Sign up to set email alerts
|

Reconfigurability Mechanisms With Scanning Rate Control for Omega-Bianisotropic Huygens’ Metasurface Leaky-Wave Antennas

Abstract: In this paper, different reconfigurability mechanisms are proposed to scan the pointing direction at a fixed frequency of recently-proposed leaky-wave antennas based on omega-bianisotropic Huygens' metasurfaces. The tunability of both the waveguide height and the dielectric permittivity of the substrate filling the waveguide are studied, extracting theoretical expressions to predict the dependence of the beam pointing direction with the design parameters. It is shown that it is possible to control the scanning… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…In this paper, the feeding network is designed to scan from −45 • to 45 • as f 1 = 3GHz and f 2 = 9GHz. Using expression (11), it can be calculated that the value of d max should be less than 19.53 mm to avoid grating lobe. So, the distance is chosen as 19.5 mm.…”
Section: B Crlh Tlsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this paper, the feeding network is designed to scan from −45 • to 45 • as f 1 = 3GHz and f 2 = 9GHz. Using expression (11), it can be calculated that the value of d max should be less than 19.53 mm to avoid grating lobe. So, the distance is chosen as 19.5 mm.…”
Section: B Crlh Tlsmentioning
confidence: 99%
“…Additionally, metasurfaces have been used to design LWAs [10]- [13]. In [10] and [11], a novel concept of a leaky-wave antenna is proposed using the Huygens' metasurfaces. With the appearance of CRLH-metamaterial, the LWAs can realize a new function of generating alterable patterns in different frequencies [14]- [17].…”
Section: Introductionmentioning
confidence: 99%
“…In [6] it was demonstrated that omega-type bianisotropic Huygens' metasurfaces (BHMSs) only need to satisfy a local power conservation condition between the fields on both sides of the metasurface to achieve arbitrary transformations. In this sense, the use of this type of BHMSs has been studied in previous works from some of the authors in order to transform a guided field into a leaky-wave radiated one [7], [8]. This way, the independent control of both wavenumber components was achieved, along with several degrees of freedom in the LWA parameters selection.…”
Section: Introductionmentioning
confidence: 99%
“…34 There has been growing interest in developing planar LWAs due to several advantages, including narrow and high directive beams, frequency-dependent beam scanning capability, smaller unit cell size, modest feeding network, and easier manufacturing. [35][36][37][38] Among planar LWAs, another approach to enhance the capability of the LWAs is to utilize a composite right/ left-handed (CRLH) unit cell. [39][40][41] By realizing the CRLH transmission line, continuous beam scanning of the LWA from backward to forward is achieved.…”
Section: Introductionmentioning
confidence: 99%
“…The concept of a metamaterial‐based antenna, such as a leaky wave antenna (LWA), had been previously investigated 34 . There has been growing interest in developing planar LWAs due to several advantages, including narrow and high directive beams, frequency‐dependent beam scanning capability, smaller unit cell size, modest feeding network, and easier manufacturing 35‐38 . Among planar LWAs, another approach to enhance the capability of the LWAs is to utilize a composite right/left‐handed (CRLH) unit cell 39‐41 .…”
Section: Introductionmentioning
confidence: 99%